Differential neuroimaging indices in prefrontal white matter in prenatal alcohol‐associated ADHD versus idiopathic ADHD. Issue 12 (29th January 2019) - O'Neill, Joseph; O'Connor, Mary J.; Yee, Victor; Ly, Ronald; Narr, Katherine; Alger, Jeffrey R.; Levitt, Jennifer G.
Abstract : Background: Attention deficit‐hyperactivity disorder (ADHD) is common in fetal alcohol spectrum disorders (FASD) but also in patients without prenatal alcohol exposure (PAE). Many patients diagnosed with idiopathic ADHD may actually have ADHD and covert PAE, a treatment‐relevant distinction. Methods: We compared proton magnetic resonance spectroscopic imaging (MRSI; N = 44) and diffusion tensor imaging (DTI; N = 46) of the anterior corona radiata (ACR)—a key fiber tract in models of ADHD—at 1.5 T in children with ADHD with PAE (ADHD+PAE), children with ADHD without PAE (ADHD−PAE), children without ADHD with PAE (non‐ADHD+PAE), and children with neither ADHD nor PAE (non‐ADHD−PAE, i.e., typically developing controls). Levels of choline‐compounds (Cho) were the main MRSI endpoint, given interest in dietary choline for FASD; the main DTI endpoint was fractional anisotropy (FA), as ACR FA may reflect ADHD‐relevant executive control functions. Results: For ACR Cho, there was an ADHD‐by‐PAE interaction ( p = 0.038) whereby ACR Cho was 26.7% lower in ADHD+PAE than in ADHD−PAE children ( p < 0.0005), but there was no significant ACR Cho difference between non‐ADHD+PAE and non‐ADHD−PAE children. Voxelwise false‐discovery rate (FDR)‐corrected analysis of DTI revealed significantly ( q ≤ 0.0101–0.05) lower FA in ACR for subjects with PAE (ADHD+PAE or non‐ADHD+PAE) than for subjects without PAE (ADHD−PAE or non‐ADHD−PAE). There was no significant effect of ADHD on FA. Thus, in overlapping samples, effects of PAE on Cho and FA were observed in the same white‐matter tract. Conclusions: These findings point to tract focal, white‐matter pathology possibly specific for ADHD+PAE subjects. Low Cho may derive from abnormal choline metabolism; low FA suggests suboptimal white‐matter integrity in PAE. More advanced MRSI and DTI—and neurocognitive assessments—may better distinguish ADHD+PAE from ADHD−PAE, helping identify covert cases of FASD.